The birth of the Gondwanide arc: Insights into Carboniferous magmatism of the North Patagonian Andes (Argentina) - Yoya, María Belén (2023)
New geological, structural, and geochemical information was obtained for the late Paleozoic basement of the North Patagonian Andes. The studied rocks are mainly formed by foliated diorites and gabbro-diorites with a primitive continental arc signature, according to trace elements patterns. Similar petrological and structural characteristics, together with previously reported ages between ca. 330 and 323 Ma, permit the correlation of these rocks with plutonic bodies located in the North Patagonian Andes, North Patagonian Massif and Cordillera de la Costa of Chile, documenting the onset of Gondwanide subduction along the proto-Pacific margin of Gondwana between ca. 37 and 45°S. Geochemical and geochronological data, together with field evidence, suggest mafic magma replenishment during the construction of this large batholith. The presence of sheeted zones and magmatic fabrics allow to interpret pluton emplacement in a highly coupled system linked with a tectonically active setting, under pressure conditions of ca. 6 ± 1 Kbar.